The Influence of Self Service Technology, Customer Intimacy and Customer Delight on Customer Lotalty With Customer Bonding as An Intervening Variable - Nevia Ramadhani; Imanda Firmantyas Putri Pertiwi (Social Science Studies, 2023)
This study aims to determine how strong the influence of Self Service Technology, Customer Intimacy and Customer Delight on Customer Loyalty with Customer Bonding as an intervening variable. This study uses a quantitative method by processing primary data obtained through distributing questionnaires to the public who are customers of Bank Muamalat KCP Salatiga. The samples taken were 100 respondents, using purposive sampling technique. Then the results obtained were processed with SPSS version 20. The analysis used included descriptive statistical tests, instrument tests, path analysis regression tests, classical assumption tests, model accuracy tests and hypothesis testing. Based on the test results obtained results: self service technology has a positive effect that is not significant on customer loyalty. Customer intimacy has a significant positive effect on customer loyalty. Customer delight has an insignificant negative effect on customer loyalty. Customer bonding has a significant positive effect on customer loyalty. Self service technology does not have a significant positive effect on customer bonding. Customer intimacy has a significant positive effect on customer bonding. Customer delight has a negative effect that does not significantly affect customer bonding. Self service technology and customer delight do not mediate customer loyalty with customer bonding. Customer intimacy can mediate customer loyalty with customer bonding.